2015
DOI: 10.1177/089875641503200302
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Crown Height to Diameter Ratio on the Force to Fracture of Canine Teeth in Dogs

Abstract: Summary Previous work suggests that the tooth height to diameter ratio (H/D) may have an influence on the fracture resistance of dog canine teeth. Thus, it can be hypothesized that canine teeth with distal abrasion or teeth already requiring pulpal manipulation may benefit from a reduction in height and that an ideal H/D exists that balances tooth fracture resistance and tooth function. Therefore, a study was performed to investigate the influence of H/D on force to fracture and probability of fracture of cani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 15 publications
(50 reference statements)
3
42
4
Order By: Relevance
“…There is an inherent variability in the ability of a tooth to resist fracture that would commonly occur during chewing on a treat or toy. The average maximum force sustained by the tested teeth was higher than what has previously been reported for strategically important teeth 2 (21). The range of data was not unexpected when published information on the fracture performance of human teeth (22) or the fracture behavior of canine teeth of dogs under pulling forces is considered (18).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…There is an inherent variability in the ability of a tooth to resist fracture that would commonly occur during chewing on a treat or toy. The average maximum force sustained by the tested teeth was higher than what has previously been reported for strategically important teeth 2 (21). The range of data was not unexpected when published information on the fracture performance of human teeth (22) or the fracture behavior of canine teeth of dogs under pulling forces is considered (18).…”
Section: Discussioncontrasting
confidence: 68%
“…For the purpose of evaluating the potential effects of material texture on the risk of inducing a maxillary fourth premolar tooth fracture during chewing, it is necessary to combine the referenced knowledge for chewing forces with an understanding of the forces required to induce a clinically observed tooth fracture. Mechanical testing has previously been conducted on extracted canine teeth from dogs, using a universal materials testing machine after potting the teeth in acrylic and applying the force at a speed of 1 mm/min to the disto-occlusal line angle at an angle of 45° to the long axis of the crowns (21). The mean forces required to fracture canine teeth ranged from 494 to 630 N depending on the crown height to diameter ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 However, the recommendation for a higher height/diameter ratio for crown preparation has been subsequently contradicted. 36 Additionally, this review concluded that the…”
Section: Figurementioning
confidence: 99%
“…Along with multiple anesthetic episodes come additional costs to the client related to equipment, instruments and materials, and pertinent laboratory fabrication fees. 36 Adjunct periodontal surgery and crown preparation may mean time "off work" that could interfere with training or the on-duty schedule of working dogs. It is recommended that prosthodontic therapy should be performed on a case-by-case basis with the clients understanding the associated risks and financial requirements.…”
Section: Figurementioning
confidence: 99%